An Expanded Survey of the Moth PBP/GOBP Clade in Bombyx mori: New Insight into Expression and Functional Roles - Guo, Xia; Xuan, Ning; Liu, Guoxia; Xie, Hongyan; Lou, Qinian; Arnaud, Philippe; Offmann, Bernard; Picimbon, Jean-François (Frontiers in Physiology, 2021)
We studied the expression profile and ontogeny (from the egg stage through larval stages and pupal stages, to the elderly adult age) of four OBPs from the silkworm moth, Bombyx mori. We first showed that male responsiveness to female sex pheromone in the silkworm moth B. mori does not depend on age-variation. Whereas, the expression of BmorPBP1, BmorPBP2, BmorGOBP1 and BmorGOBP2 varies with age. The expression profile analysis revealed that the studied OBPs are expressed in non-olfactory tissues at different developmental stages. In addition, we tested the effect of insecticide exposure on the expression of the four OBPs studied. Exposure to a toxic macrolide insecticide endectocide molecule (abamectin) led to modulated expression of all the four genes in different tissues. Higher expression of OBPs were detected in metabolic tissues such as the thorax, gut and fat body. All these data strongly suggest some alternative functions for these proteins other than olfaction. Finally, we carried-out ligand docking studies and reported that PBP1 and GOBP2 have the capacity of binding vitamin K1 and multiple different vitamins.